5t(10-3t)=

Simple and best practice solution for 5t(10-3t)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t(10-3t)= equation:


Simplifying
5t(10 + -3t) = 0
(10 * 5t + -3t * 5t) = 0
(50t + -15t2) = 0

Solving
50t + -15t2 = 0

Solving for variable 't'.

Factor out the Greatest Common Factor (GCF), '5t'.
5t(10 + -3t) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0

Subproblem 2

Set the factor '(10 + -3t)' equal to zero and attempt to solve: Simplifying 10 + -3t = 0 Solving 10 + -3t = 0 Move all terms containing t to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -3t = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -3t = 0 + -10 -3t = 0 + -10 Combine like terms: 0 + -10 = -10 -3t = -10 Divide each side by '-3'. t = 3.333333333 Simplifying t = 3.333333333

Solution

t = {0, 3.333333333}

See similar equations:

| 7/x-4=14/6 | | -5(4x-1)=-3x-6 | | 7-k=5 | | -7x-13+9x-19=-4 | | -1=2(j-8)+1 | | 10(s-6)=-146 | | 32-4x=18-6x | | 10y^2+90y=0 | | H=15t-4.9t^2+3 | | -2(8x+3)=3x | | 4x-x=7squared | | 2n-8+6n=-14+8n | | 2z-15+3z=5-5z+10 | | 4(b-12)+1=17 | | 2x+32=60 | | 11+3x=15+9x-3x | | 2(m+1)+2=10 | | X-5x=6-2x+5 | | -24x+18=4 | | 3v+6=0 | | -7+x=7+9-5 | | -16=5v+11 | | 9x+6=3(x-4) | | -6+7k=1+7k | | 0.2x-1.6=2.4x+2.7 | | -8w+4=0 | | 2(r+7)=-4 | | 4m-3n=8form | | 7x+263.5=2717 | | 5b+3(b-4)=2(y+3) | | 3x+6(-2)=24 | | 0.6x+1.9=5 |

Equations solver categories